The relationship between higher education and employment in Portugal - David, Fátima (2016)
The purpose of this research is to discuss the relationship between higher education and employment in Portugal. The Constitution of the Portuguese Republic of April 2, 1976, gives women (and men) a right to equal opportunities for school success, to access to the higher education and to better working conditions. However, despite the expansion of the education system, showing the rapid progress in improving baseline qualifications, women's educational attainment in certain areas remains a challenge. Thus, this research explores the development of the higher education system, examines the nature and implication of organizational change for graduates and assesses what attributes graduates will need in the next decade. Methodologically, this research relies on two different approaches. The first approach takes the form of a literature review, based on the legal regime of the Portuguese higher education system, considering that, according to Decree-Law nº 402/73 of August 11, Portugal promoted the democratization of education that was been consolidated in the expansion and diversification of higher education to match the need to ensure economic development of the country, requiring an ever higher number of technicians and administrators with higher education. The second approach takes the form of a descriptive statistical analysis, supported on the information provided by the Portuguese Public Employment Service (in Portuguese, Instituto do Emprego e Formação Profissional - IEFP) web portal, to provide a glimpse of the ‘employability’ agenda in Portugal. Additionally, supported on the statistical information provided by National Statistical Institute (in Portuguese, Instituto Nacional de Estatística - INE) and Portuguese Ministry of Education and Science that show the diversification of the higher education system and it increases the qualification of the Portuguese citizens, in general. In this sense, the research provides empirical evidence about the social dimension of the higher education system at the same time highlighting the influence of this aspect in the nature and implication of organizational change for graduates and assesses what attributes graduates will need in the next decade. Indeed, the results of the research show: young women hold a higher qualification than men with the same age; gender differences still exist in certain fields, with more men studying science, informatics and engineering, and with women dominating education, health and social protection; despite their higher educational attainment, young women still have lower employment rates than men; women with higher education earn lower of their male peers’ earnings, in consequence of the under-representation of women in some fields of higher education, which are highly rewarded by the labor market. Thus, these results confirm those presented by the Organisation for Economic Co-operation and Development (OECD) in March of 2015 on a study with 36 countries.